Enhancing Employee Performance: Rewards, Training, and Work Ethics at the Education Office of the Bangka Belitung Islands Province - Yahya, Yanda; Hamsani, Hamsani; Reniati*, Reniati (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This research was motivated by the existing condition where employees have not been able to work optimally in a government institution. The study aims to analyze and examine the influence of rewards, training, and work ethic on Employee Performance in the Education Authority of Bangka Belitung Island Province. This research is descriptive in nature. The quantitative research method was employed because the data obtained are numerical and derived from questionnaires, with a total sample size of 64 respondents, determined through a saturated sample method. The analytical model used was multiple linear regression, with t-tests, f-tests, and coefficients of determination. The research results indicate that rewards, training, and work ethic, individually, have a positive and significant impact on the performance of employees in the Education Authority of Bangka Belitung Island Province. Through this research, institutions can review the factors leading to low employee performance in the variables of rewards, training, and work ethic. Keywords: Reward; Training; Work Ethic; Employee Performance; Education Office